(untitled) (Journal of Rangpur Medical College, 2024)
Background: Hepatitis B (HBV), and Hepatitis C viral HCV) infections are the major health problems worldwide. Patients undergoing hemodialysis (HD) are more vulnerable to acquired such infections than the general population. Objective: To evaluate the prevalence of HBV and HCV infection in hemodialysis patients and the association of number of dialysis and history of blood transfusion with risk of HBsAg and HCV infection. Methods: This cross-sectional observational study was conducted in inpatient and outpatient department of Nephrology and Medicine, Rangpur Medical College and Hospital, Rangpur, Bangladesh from December 2021 to May 2022. A total of 80 diagnosed case of End Stage Renal Disease (ESRD), who underwent dialysis during the study period were included in the study. Complete history was taken either from patient or accompanying attendants. Collected data were classified, edited, coded and entered the computer for statistical analysis by using SPSS version 23. Results: Out of 80 hemodialysis patients, mean age was found 42.6±8.6 years with range from 21 to 59 years. Male patients were predominant (72.50%) with male to female ratio was 2.6:1. The prevalence of HBV and HCV infection was found in 8.75% and 11.25% respectively. Frequency of dialysis and history of blood transfusion was not significantly associated with risk of HBsAg and HCV infection. Conclusion: The prevalence of HBV and HCV infection was found in 8.75% and 11.25% respectively. Frequency of dialysis and history of blood transfusion was not significantly associated with risk of HBsAg and HCV infection. J Rang Med Col. September 2024; Vol. 9, No. 2: 72-77